COVID – 19 Pandemic Periods and India's MSME Sector - K. Ramesh Kumar (International Journal of Small and Medium Enterprises and Business Sustainability, 2023)
The COVID–19 pandemic has had an abrupt impact on India’s micro, small, and medium-sized enterprises (MSMEs). As per the data available from the Central Statistical Office, the share of MSMEs in gross value added is 33 percent and the share in the total gross domestic product is 30 percent at all India levels. In terms of employment after agriculture, the MSMEs provide more than 110 million jobs in both rural and urban areas, it is nearly 9 percent of the total population of India, and the largest employment provider after the primary sector. The MSMEs in India are led by three important sectors, namely, Manufacturing, Electricity, Trade, and other services. After the declaration of WHO, in India, the lockdown was enforced by the Union and State governments in two waves of COVID-19 with full and partial restrictions. The small and medium- scale enterprise was severely encountered in both waves (2020 and 2021). Before COVID-19, the Demonitation and GST (good and service tax) regulations of the Union government had negatively hit the business of MSMEs. COVID-19 considerably affected the MSME in various forms viz., disruptions of the supply chain, the shutdown of demand and supply side markets, mental health issues, war between business and life for balancing, inadequate finances to meet day-to-day life business like rental and electricity charges, wages and compensation to workers. After the unlocking of the first wave, the MSMEs started their business gradually up to December 2020; however, the second wave started in February 2021 and hit the MSME business at the national level. The study aims to understand the impact of COVID-19 on India’s MSME sectors by analyzing the value of output, employment and trade, and other related sub-sectors of MSMEs. This study also highlights the significant policy matters to recover the unsoundness of MSMEs sectors under COVID-19 pandemic times and in different phases of national level lockdown. The results show the manufacturing growth rate was moved to negative 22 percent in March 2021 and 0.1 percent in February 2021. The Union government has introduced many financial packages to battered businesses. Finally, the study concluded that the sustainability of economic growth will depend on the recovery and strengthening of the MSME sectors.